Joper Chicken and Cage-Free Layer Farmers Group Business Development in Sleman Regency through the Social Capital Approach - A'yun, Annisa' Qurrotun; Haryadi, Fransiskus Trisakti Haryadi; Andarwati, Siti; Jihadhan Wankar, Tian; Baskara, Aji Praba (Faculty of Animal Science, Universitas Brawijaya, 2025)
Sleman Regency focuses on developing joper chicken and cage-free layer farming businesses to promote sustainability and ethical farming practices, ultimately enhancing livelihoods and food security in the region. Social capital, as an intangible asset, plays a crucial role in facilitating effective collaboration and overcoming challenges in livestock businesses. Therefore, this research aimed to analyse the model of business development for joper and cage-free layer farming, as well as the total social capital from both businesses collectively. Primary data were collected through direct interviews and focus group discussions (FGDs) with all active members and farmer group management. The analysis of the business model was conducted via a business development plan approach, whereas the social capital employed descriptive analysis with a Likert scale. The results showed that government support includes technical training, capital assistance in the form of chicks and feed, and business monitoring. All these activities help farmers manage their poultry business. This guidance provides farmers with greater opportunities to improve their business management skills, address production challenges, and expand their marketing networks. Overall, joper chicken and cage-free layer farming have different business development models, specifically in the procurement of production inputs and product marketing. However, both businesses collectively demonstrated strong social capital across all aspects (trust, norms, reciprocity, and network). This social capital enables farmers to collaborate effectively, establish rules, and exchange information to improve farming benefits. This study implies that strengthening institutional support and promoting multistakeholder collaboration are essential to optimize the development of poultry farming.